Pengaruh Pengalaman Auditor, Time Budget Pressure dan Ukuran Kantor Akuntan Publik Terhadap Audit Report LAG Pada Auditor Kantor Akuntan Publik Di Kota Surabaya - Dewi Sutjahyani (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
The job of the auditor is to provide useful information, therefore when the audited report is delayed it will reduce the use value of the financial statements presented. Therefore, it is important to identify and have a deeper look at several factors related to the occurrence of audit report lag. Thus, it is necessary to study whether these factors significantly influence the audit report lag. This is important because the audit report lag phenomenon can reduce client interest and affect the reputation of auditors and public accounting firms where auditors work. Hypothesis 1 in this study is rejected, this means that the experience of auditors does not significantly affect the Audit Report Tag. work and the number of inspection tasks. The experience variable does not have a significant effect because audit quality is not determined by the length of work and the number of audit tasks. Hypothesis 2, namely that time budget pressure has an effect on audit report lag, is rejected. Time budget pressure is vital in the process of completing an audit report. In this case the time budget pressure does not have a significant effect because the budget pressure is determined when planning to determine the audit task but the implementation of the audit can be different influenced by the existing situation. For example during a pandemic, uncontrollable situations lead to leeway in the completion of audited reports. So that the existing time budget pressure must be adjusted. The hypothesis in this study is accepted, this is because the size of KAP basically determines the level of efficiency and effectiveness of each auditor's task. In medium and large KAPs, there is usually a structured system and maturity from the audit planning process to the audit. This is because large public accounting firms usually try to maintain quality and reputation to keep their clients interested